PENGEMBANGAN APLIKASI CANVA SEBAGAI MEDIA PEMBELAJARAN MENULIS SURAT UNTUK PESERTA DIDIK KELAS VII SMP - Hendrawati, Mutiara; Yanuarsih, Sri; Mu’minin, Moh. (Universitas Tanjungpura, 2024)
Learning media is a tool used as an intermediary to convey messages or information from the sender to the recipient, so that it can stimulate students' attention, feelings, thoughts and interest in the learning process. The aim of this research is to test the validity of developing the Canva application as a learning medium that is suitable for use by teachers and students of class VII SMP by involving validators. Apart from that, it is also able to test the practicality of using Canva as a learning medium and increase students' understanding of the material presented. This research is a type of development research or Research and Development (RD) which aims to develop a product so that it is more effective when used. Data collection techniques in this research are observation, interviews, and validation instruments. The method in this research is a quantitative method for data scores obtained from validators and a qualitative method for data analysis and suggestions given. The results of this research prove that the percentage figures and criteria analysis from validators state that the development of the Canva application as a learning media is suitable for use because it has carried out validation tests by material, language and media experts. This is based on the validation test scores of material experts and language experts with good classification presentation results and media statements revised as necessary. Meanwhile, the media expert validation test with very good classification presentation results and media information did not need to be revised.